Exploring health care professionals views on alternative approaches to cancer follow-up and barriers and facilitators to implementation of a recovery package - Williamson, S; Beaver, K; Langton, S (Elsevier, 2020)
Purpose To meet the long-term needs of cancer survivors the focus of recent cancer care reform in the United Kingdom (UK) has been the implementation of alternative follow-up strategies to relieve the growing pressures threatening to overwhelm cancer services. In 2013, the UK's National Cancer Survivorship Initiative recommended an integrated package of care called the Recovery Package to meet cancer survivors' psychosocial and information needs and supported self-management.